Multirate filtering for digital signal processing [ MATLAB applications - Milic´, Ljiljana , 1939- (Hershey, Pennsylvanial : Information Science Reference, 2009)
"This book covers basic and the advanced approaches in the design and implementation of multirate filtering"--Provided by publisher
"Premier reference source"--Cover
Description based on print version record
Includes bibliographical references and index
Keywords: Electric filters, Bandpass -- Computer simulation; Multiplexing -- Computer simulation; Signal processing -- Digital techniques -- Data processing; Signal processing -- Digital techniques -- Mathematics